Kafe, Kopi dan Karir: Interpretasi Pilihan Karir Sebagai Coffee Shop Content Creator - Vidya Nindhita; Hapsari Puspita Rini; Kurrota Aini (Jurnal Kajian Ilmiah, 2024)
The increasing trend of public consumption of coffee products has led to many entrepreneurs entering the coffee business and coffee shops. Intense competition in the coffee business causes coffee shops to compete to be able to promote their shops, one of which is by using social media and content creators. This job focus makes individuals who choose a career as a content creator are individuals with the main characteristics of being creative and having a good advertising strategy or plan. However, it is undeniable that there are several challenges in this profession, including limited skills, very flexible working hours and questionable career certainty, as well as a lack of brand awareness in some coffee shop entrepreneurs. This study was conducted to determine the description of the career choices of content creators engaged in coffee shop content. The study used qualitative research methods with a phenomenological approach. The sampling method uses purposive sampling. Data collection in the study used a semi-structured interview method. The results revealed that the description of career choices in content creators with coffee shop content starts from the existence of career meanings to an understanding of the characteristics of work as a content creator. Other factors in career choice as an content creator are also based on support from family and the content creator community.